Analysis of Students' Creative Characters Through The Reyog Ponorogo Arts Program in Primary Schools - Retno Anjar Risnawati; St. Y. Slamet; Sandra Bayu Kurniawan (Universitas Sebelas Maret, 2024)
SDS Mutiara Hati Ponorogo established Reyog Ponorogo Art as a program for the Strengthening Pancasila Student Profile (P5) Project with the theme of local wisdom. This program not only provides an understanding of local arts and culture but also has the potential to shape students' creative character. The objectives of this research are: 1) To describe and analyze the creative character of students through the Reyog Ponorogo arts program. 2) Describe the supporting factors for students' creative character through the Reyog Ponorogo arts program: data collection techniques using interviews, observation and documentation. The subjects of this research were phase B, totalling 18 students for the 2023/2024 academic year. Critical thinking skills data was obtained from the critical thinking skills rubric. The analysis was carried out using Milles Huberman's (1984) interactive analysis technique, namely by collecting, reducing, presenting, and drawing conclusions. The research results show that The results of the research show that 1) students who take part in the Reyog Ponorogo arts program are categorized as having very creative characters. 2), supporting factors for students' creative character through the Reyog Ponorogo arts program, including: students' potential, parental support, and support from the school. In conclusion, students who take part in the Reyog Ponorogo arts program are classified as having a very creative character, which is caused by the potential of the students, support from parents, and support from the school.